2021
DOI: 10.1111/ctr.14494
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine based remote monitoring after liver transplantation: Feasible in a select group and a more stringent control of immunosuppression

Abstract: Telemedicine gained interest in liver transplant patients but focused until now on the early post-operative period. This prospective cohort study assessed feasibility, safety, and clinical beneficial effects of a telemedicine based remote monitoring program (TRMP) for the chronic follow-up of adult liver transplant recipients. Between November 2017 and August 2019, a total of 87 of the 115 selected patients (76%) started the TRMP. Over the 2 years study period, none of the patients switched to standard followu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
4

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 32 publications
0
19
0
4
Order By: Relevance
“…We also think that the use of TH in the initial transplant evaluation can shorten or substitute some of the inperson consultations, such as the transplant hepatology visit for stable chronic liver disease suffering from HCC, the psychosocial evaluation and, if a handgrip dynamometer or measurement tape is available on prior remote consultations, the nutritional assessment. Moreover, in the posttransplant setting, telemedicine offers an equally effective option for close follow-up, without differences in pertinent outcomes such as rates of graft rejection, hospital readmission, and overall mortality 47,49 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We also think that the use of TH in the initial transplant evaluation can shorten or substitute some of the inperson consultations, such as the transplant hepatology visit for stable chronic liver disease suffering from HCC, the psychosocial evaluation and, if a handgrip dynamometer or measurement tape is available on prior remote consultations, the nutritional assessment. Moreover, in the posttransplant setting, telemedicine offers an equally effective option for close follow-up, without differences in pertinent outcomes such as rates of graft rejection, hospital readmission, and overall mortality 47,49 …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in the posttransplant setting, telemedicine offers an equally effective option for close follow-up, without differences in pertinent outcomes such as rates of graft rejection, hospital readmission, and overall mortality. [47,49] Likewise to HCV, TH has shown equal efficacy in the management of HBV. [42] In patients with NAFLD, various TH modalities involving behavioral change and nutritional counseling resulted in improved or equivalent weight loss.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have demonstrated the usefulness of telehealth in heart failure and diabetic glucose regulation, exhibiting similar results to telephone follow-up and in-patient visits[ 51 ]. With regards to liver transplantation, one study showed that long-term follow-up via telehealth had comparable outcomes to in-person follow-up, with the only drawback of requiring stricter control over tacrolimus levels[ 52 ]. Importantly, 75% of physically stable transplant patients expressed interest in telemonitoring, with distance from the hospital being a major contributing factor.…”
Section: Telehealth In Liver Transplantationmentioning
confidence: 99%
“…The use of RPM in LTRs is primarily motivated by the fact that it has the potential to improve patient outcomes, including better and earlier diagnosis of complications, increase quality of life by facilitating transparency and reassurance of the current patient condition and reducing the personal consultation frequency [ 1 , 2 , 3 ]. Some telemedical remote monitoring programs do not rely on measuring devices but focus only on information exchange based on software applications using mobile devices or regular computers in solid organ transplantation recipients [ 5 ]. Only a small number of randomized controlled trials have investigated mobile health interventions in LTRs focusing on patient education, spirometry, self-management and a computer-based decision system for triage [ 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%